Partnerships for a Healthier Indonesia : Unlocking Constraints for Better Private Sector Participation - World Bank (World Bank, Washington, DC, 2021)
Indonesians have become healthier in recent decades as confirmed by the progress on key health indicators. Despite these advancements, significant challenges remain in improving maternal health and nutrition and in tackling persistent communicable diseases. As the Indonesian population grows older, new challenges are emerging. Regional and income-related inequalities in health outcomes persist. The private sector can play an important role in driving better health outcomes for all Indonesians. There has been increased utilization of outpatient and inpatient private sector health services by all Indonesians, including the poor. Of course, increased private sector involvement is not a panacea. The challenge is to manage trade-offs between equity and efficiency, growth and access to health, and private and public sector participation. Considering these trade-offs, this report investigates the opportunities and constraints to more and better private sector participation in the Indonesian health services sector.